PEMANFAATAN MEDIA INTERAKTIF BERBASIS NEARPOD PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Lavenia Permata Sari; Firman; Desyandri (STKIP Subang, 2024)
This research uses a literature study method or Systematic Literature Review (SLR) which examines the use of Nearpod-based interactive media in Pancasila education learning in elementary schools. This research aims to provide information related to the use of Nearpod-based interactive media in Pancasila education learning in elementary schools to support the learning process in the classroom. The method used is literature study where the data is data from various sources, such as journals, books, scientific papers and other libraries. This collection of data is analyzed one by one to be grouped and combined into a complete conclusion. The results of the research show that the use of Nearpod-based interactive media in Pancasila education learning in elementary schools really supports the learning process, seen from increased understanding of the material and learning outcomes, students who become more active and enthusiastic and are also very enthusiastic about learning, because of the appearance in the product The Nearpod application is interesting and also equipped with audio, video, animation, games and quizzes.